2022
DOI: 10.3389/fchem.2022.848685
|View full text |Cite
|
Sign up to set email alerts
|

Computing With Networks of Chemical Oscillators and its Application for Schizophrenia Diagnosis

Abstract: Chemical reactions are responsible for information processing in living organisms, yet biomimetic computers are still at the early stage of development. The bottom-up design strategy commonly used to construct semiconductor information processing devices is not efficient for chemical computers because the lifetime of chemical logic gates is usually limited to hours. It has been demonstrated that chemical media can efficiently perform a specific function like labyrinth search or image processing if the medium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In a number of recent papers, it has been shown that networks of interacting chemical oscillators can be trained to perform classification tasks with reasonable accuracy [45,46,49]. Let us consider a problem A defined by a set of records D A = {r n , n = 1, N}.…”
Section: Classification Type Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of recent papers, it has been shown that networks of interacting chemical oscillators can be trained to perform classification tasks with reasonable accuracy [45,46,49]. Let us consider a problem A defined by a set of records D A = {r n , n = 1, N}.…”
Section: Classification Type Problemsmentioning
confidence: 99%
“…Coupling between oscillators, indicated by arrows in Figure 3, is achieved by reactions that extend the original Oregonator model. I assume that the coupling is of the activatory type and occurs via the exchange of reactor activators between oscillators [49]. Let U i denote the activator of the ith node.…”
Section: The Model Of a Networkmentioning
confidence: 99%
“…The coupling between oscillators, indicated by two direction arrows in Figure 4A is achieved by reactions that extend the original Oregonator model. We assume that the coupling is of the activatory type and occurs via the exchange of reactor activators between oscillators (Gorecki and Bose, 2020;Bose and Gorecki, 2022). Let U i denotes the activator of the ith oscillator.…”
Section: The Clinical Data and Their Classificationmentioning
confidence: 99%
“…Evolutionary algorithms are frequently used for parameter optimization. Once optimized, even a small network can classify schizophrenia [40] or color of points on the Japanese flag [41] with accuracy exceeding 90%.…”
Section: Introductionmentioning
confidence: 99%